THE CORRELATION BETWEEN TEACHERS’ PEDAGOGICAL COMPETENCE AND STUDENTS’ LEARNING MOTIVATION IN ENGLISH - Ramadhani, Putri; Dollah, Syarifuddin; Muhayyang, Maemuna (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research aims to find out the correlation between teachers’ pedagogical competence and students’ learning motivation in English. A correlational quantitative research design was used in this research. The samples consisted of 27 students of class XI.2 from MAN 2 Polewali Mandar who were selected using a cluster random sampling technique and 3 English teachers. Data were collected through teacher competency test and questionnaire. The results of this research show that the correlation between teachers’ pedagogical competence and students’ learning motivation of rxy = 0.655 (within the range 0.60-0.799), where the two variables have a high correlation and positively correlated. It can be concluded that the hypothesis which states that there is a correlation between teachers’ pedagogical competence and students’ learning motivation in English is accepted. This means that the higher the teachers’ pedagogical competence, the higher the level of students’ learning motivation.